A preliminary investigation on the antibacterial activity of Kasla (Jatropha gossypifolia) roots. - Morales, Cristine Nacario
Aqueous and alcoholic extracts of kasla roots were tested on four bacteria namely: B. subtilis BIOTECH 1514, E. coli ATCC 8739, O. aeruginosa BIOTECH 1335, and Staphylococcus aureus BIOTECH 1526. All the test organisms were subjected to the Kirby-Bauer Disk Diffusion method. , Results showed that the alcoholic extract prepared by soaking pounded roots on a 1:1 (w/v) ratio caused strong inhibitory effect on E. coli, a moderate inhibitory effect on S. aureus and elicited a weak response from P. aureginosa. The aqueous extract likewise resulted in a strong inhibitory action on E. coli and a weak response from P. aeuruginosa and S. aureus. B. subtilis showed a negative response to both extracts. The minimum inhibitory concentration (MIC) of alcoholic and aqueous extracts was also determined for E. coli, P. aeruginosa, and S. aureus. The MIC for the alcoholic extract was also observed to be on the fith dilution tube for all organisms. This represented 6.25 crude extract. The aqueous extract showed MIC on the third dilution tube containing 25 of the original extract in E. coli, and MIC on the second dilution tube containing 50 of the original extract for both P. aeruginous and S. aureus. This shows that the alcoholic extract is more effective in inhibiting the growth of the three susceptible bacteria.